Analisis Keterampilan Pemecahan Masalah Melalui Model Project Based Learning Materi Gelombang Bunyi pada Alat Musik Patrol Jember - Ainun Fitriya Nurhasanah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Physics learning which tends to be abstract and does not utilize local wisdom, has an impact on students' low problem solving skills. The low problem solving skills of high school students in physics indicate the need for more contextual and real-life experience-based learning innovations. The purpose of this study was to analyze students' problem solving skills through the application of the Project Based Learning (PBL) model integrated with the local wisdom of Jember patrol musical instruments in sound wave material. This study was a qualitative study with a phenomenological design. The research subjects consisted of 12 students, and data were collected through observation, interviews, and student worksheets. Data analysis followed Creswell's stages through the process of data organization, coding, theme development, and validation using triangulation. The results of the study indicate that the problem solving abilities of the majority of students' are in the good category. In the indicators of understanding the problem, devising a plan, and carrying out the plan, the majority of students were in the good category, while in the indicator of looking back, they were in the poor category because students were not accustomed to evaluating the results of their results, thus requiring adaptation and guidance in reviewing the steps and results obtained. These findings provide a basis and inspiration for further research to pay more attention to students' problem-solving skills in the development of contextual learning and the integration of local wisdom in physics education.
Validasi dan Finalisasi Repositori File 06 Juli 2026_Kholif Basri
Keywords: Problem Solving Skills; Project Based Learning; Patrol Musical Instruments; Sound Waves.